Kepemimpinan Melayani dan Komitmen Afektif pada Perubahan di Perguruan Tinggi Indonesia: Model Mediasi Kepemilikan Psikologikal - Halim, M; Umaroh, Rodhiah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Based on self-determination theory, this study identified the effect of servant leadership on the affective commitment to change of lecturers in Indonesian. This study empirically examined the specificity of the servant leadership construct when compared with other positive leadership constructs. The mediation effect of psychological ownership of lecturers was also examined. A total of 321 responses were analyzed using a two-stage structural equation modeling (SEM) approach to confirm factors and test the study hypotheses. The results showed that the level of servant leadership had a significant effect on psychological ownership, and servant leadership had a significant indirect effect on affective commitment to change only through psychological ownership of the lecturers. Research limitations and implications are discussed and future directions of research are suggested